Demographic change and consumption: A long-term simulation analysis - Silvia Stiller (Hamburg Institute of International Economics (HWWA), 2000)
This study investigates the influence of the demographic ageing process in Germany on the long-term economic growth path. For this purpose a macroeconomic simulation model which combines demographic forecasts with a modified Ramsey growth model is applied. Special focus is put on the consumption effects of population ageing and the potential to counter those by rising fertility or permanent immigration. The simulation results illustrate that in the medium and in the long terms per capita consumption is among all demographic scenarios lower than without demographic changes. Permanent immigration can retard the consumption decrease. Rising fertility even reinforces the decline of consumption in the examined period of time. – – Das Diskussionpapier beschäftigt sich mit dem Einfluss der demographischen Alterung auf den langfristigen Wachstumspfad in Deutschland. Die Analyse basiert auf einem makroökonomischen Simulationsmodell, welches Bevölkerungsvorausberechnungen mit einem modifizierten Ramsey-Modell kombiniert. Die Auswertung der Simulationsergebnisse konzentriert sich erstens auf die Konsumeffekte der zukünftigen Umbrüche in der Bevölkerungsstruktur. Zweitens wird untersucht, ob steigende Fertilität oder permanente Zuwanderung den ökonomischen Effekten der demographischen Alterung entgegenwirken können. Die Ergebnisse zeigen, dass der Pro-Kopf-Konsum unter Annahme demographischer Veränderungen mittel- und langfristig geringer ist als ohne Veränderungen in der Bevölkerungsstruktur. Permanente Zuwanderung kann dem Rückgang des Pro-Kopf-Konsums entgegenwirken. Steigende Fertilität verschärft den Konsumrückgang in dem berücksichtigten Zeitraum.
Keywords: E17; E21; J11; 330; Population Ageing; Consumption; Growth; Gesamtwirtschaftlicher Konsum; Alternde Bevölkerung; Bevölkerungsökonomie; Bevölkerungsstruktur; Simulation; Theorie; Deutschland